A mangrove nitrous oxide sink attenuates methane climate impacts - Alex Cabral; Juliana Hayden; Bárbara Viana; Marcos deAlmeida; Tiago Passos; Roberto Barcellos; Stefano Bonaglia; Vanessa Hatje; Isaac R. Santos (Limnology and Oceanography Letters)
Abstract We resolve mangrove nitrous oxide (N2O), methane (CH4), and carbon dioxide (CO2) vertical exchange with the atmosphere and lateral exchange with the ocean. Our new observations in Brazil were combined with literature data to reassess the overall mangrove carbon sequestration potential. The pristine mangrove creek was a source of CO2 and CH4, and a sink for N2O. The CO2‐equivalent N2O uptake offset up to 71% of local CH4 emissions. Global mangrove N2O sinks offset 34% of water–air CH4 emissions, potentially absorbing 0.6 Tg CO2 equivalents per year. Overlooking lateral exchange led to a large underestimation of mangrove N2O and CH4 fluxes. Previous observations in mangroves receiving nitrogen‐rich freshwater may have misattributed N2O sources. Pristine seawater‐dominated mangroves typically act as N2O sinks while those influenced by anthropogenic inputs are sources. Overall, the observed N2O sink further enhances the net climate benefit of mangroves.